Potential safety signal of pregnancy loss with vascular endothelial growth factor inhibitor intraocular injection: A disproportionality analysis using the Food and Drug Administration Adverse Event Reporting System - Sakai, Takamasa; Mori, Chiyo; Ohtsu, Fumiko (Frontiers in Pharmacology, 2022)
Objectives: Intraocular administration of vascular endothelial growth factor (VEGF) inhibitors may be associated with pregnancy loss. However, little is known about intraocular anti-VEGF therapy during pregnancy. Here, we conducted a pharmacovigilance study using a spontaneous reporting database to evaluate the relationship between intraocular VEGF inhibitors and pregnancy loss. Methods: We used the JAPIC AERS database which is composed of the Food and Drug Administration Adverse Event Reporting System (FAERS) dataset preprocessed by the Japan Pharmaceutical Information Center (JAPIC) to investigate the VEGF inhibitors ranibizumab, aflibercept, and bevacizumab. Disproportionality analyses were conducted for VEGF inhibitors and pregnancy loss. The lower limit of the 95% confidence interval (CI) of the reporting odds ratio (ROR) > 1 and a minimum of three reported cases of pregnancy loss were the detection criteria used in the current study. Results: In the FAERS, 19 pregnancy loss cases were reported for ranibizumab with an ROR of 4.44 (95% CI: 2.42–8.16), 6 for intraocular bevacizumab with an ROR of 32.25 (95% CI: 3.88–267.9), and 4 for intraocular aflibercept with an ROR of 5.37 (95% CI: 1.34–21.49). All these drugs met the detection criteria. Conclusions: Potential safety signals of pregnancy loss were obtained from intraocular administration of VEGF inhibitors during pregnancy. These signals should be validated using a causal design study.